The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1177/1178224219875738
|View full text |Cite
|
Sign up to set email alerts
|

The need to distinguish between different forms of oral nutrition refusal and different forms of voluntary stopping of eating and drinking

Abstract: Voluntary stopping of eating and drinking (VSED) is a well-known phenomenon among palliative care professionals. This study intent to distinguish between different forms of VSED. In a qualitative interview study 18 relatives were interviewed about their experiences of caring a person during VSED. Different forms of oral nutrition refusal and different forms of VSED were found and described. The study results help members of the multidisciplinary team to manage the situation appropriately.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 26 publications
0
21
0
Order By: Relevance
“…VSED is the free decision of a person to refuse the intake of food and fluids with the intention of ending their life prematurely (Bernat et al, 1993; Byock, 1995; Ivanović et al, 2014; Mattiasson & Andersson, 1994; Quill et al, 1997). It is not equivalent to, for example, loss of appetite during the dying process, refusal to eat due to mental illness (e.g., dementia, anorexia), eating disorders (e.g., dysphagia), or hunger strike (Stängle et al, 2019c). According to the definition of Ivanović et al (2014), an essential prerequisite for being able to carry out VSED is the ability of the person to wish to die (Grisso, & Appelbaum, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…VSED is the free decision of a person to refuse the intake of food and fluids with the intention of ending their life prematurely (Bernat et al, 1993; Byock, 1995; Ivanović et al, 2014; Mattiasson & Andersson, 1994; Quill et al, 1997). It is not equivalent to, for example, loss of appetite during the dying process, refusal to eat due to mental illness (e.g., dementia, anorexia), eating disorders (e.g., dysphagia), or hunger strike (Stängle et al, 2019c). According to the definition of Ivanović et al (2014), an essential prerequisite for being able to carry out VSED is the ability of the person to wish to die (Grisso, & Appelbaum, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…VSED is an option when a person consciously and voluntary decides to bring about death by stopping eating and drinking (1,13). It differs significantly from other forms of food refusal (14), where the person has no intention of dying (13,15,16). In Switzerland, VSED was first included in the Swiss Academy of Medical Sciences' (SAMS) guidelines for "Management of dying and death" in 2018 (17).…”
Section: Introductionmentioning
confidence: 99%
“…Many participants had accompanied people during VSED; overall, patients are granted the right to medical and nursing care, and VSED is often considered an autonomous and "good" way to die (1,8,11,12,32). Although there are few qualitative studies (13), previous research indicated that accompanying a person during VSED is an individual decision (33), and that there is an implicit or unspoken form of VSED where the person does not talk about their intention or even hides it from others (14). The existing evidence is not sufficient to derive practical recommendations for health professionals.…”
Section: Introductionmentioning
confidence: 99%
“… 5 , 9 , 20 , 21 VSED must be clearly distinguished from artificial feeding, 22 from external influences that impair food intake (e.g., pain, malnutrition ), 23 25 and from psychological impairments (e.g., dementia, depression). 26 , 27 People choosing VSED are mostly women (62%) and can be found in all age groups; however, most individuals who opt for VSED (48%–70%) are aged 80 years or older. 3 , 7 , 19 , 28 …”
Section: Introductionmentioning
confidence: 99%